Exercise intensity prescription in cancer survivors: ventilatory and lactate thresholds are useful submaximal alternatives to VO2peak - Schneider, Justine; Schlüter, Kathrin; Sprave, Tetyana; Wiskemann, Joachim; Rosenberger, Friederike (Supportive care in cancer, 2020)
Most studies with cancer survivors use percentages of peak oxygen uptake (VO2peak) for intensity prescription. Lactate or ventilatory thresholds might be useful submaximal alternatives, but this has never been investigated. Therefore, we aimed at comparing three training sessions prescribed using %VO2peak (reference), lactate thresholds, and ventilatory thresholds in terms of meeting the vigorous-intensity zone, physiological, and psychological responses.